ANALISIS PREDIKSI KEBANGKRUTAN DENGAN METODE ALTMAN, SPRINGATE, ZMIJEWSKI, FOSTER, DAN GROVER PADA EMITEN JASA TRANSPORTASI - Ria Effendi (Ma Chung Press, 2018)
This study aims to determine the level of potential bankruptcy of a company. In this study, the company under study is transports company listed on the BEI. The companies include PT Express Transindo Utama Tbk (TAXI), PT Weha Transportasi Indonesia Tbk (WEHA), PT Zebra Nusantara Tbk (ZBRA), PT Steady Safe Tbk (SAFE) and PT Adi Sarana Armada Tbk (ASSA). To research the company, researchers use 5 methods, namely the method of Altman, Springate, Zmijewski, Foster, and Grover and as a first step in knowing the bankruptcy signal of the company early. This type of research is descriptive quantitative. The data source used is secondary data. Population in this research is public transportation service issuer amounting to 33 transportation service company. The sample of research is using purposive sampling method, with 5 service companies of land transportation as sample. The results of this study indicate that there are 5 methods used and generally have differences in the results of calculations, as well as publicly listed land transportation service companies have the potential to experience bankruptcy. Of the 5 methods used that are most accurate in determining the prediction of freedom is the Springate method.